High throughput newborn screening for Sickle cell disease - application of two-tiered testing with a qPCR-based primary screen = Hochdurchsatz-Neugeborenenscreening auf Sichelzellkrankheit - Anwendung einer zweistufigen Analytik mit einem qPCR-basierten Primärscreening - Janda, Joachim; Hegert, Sebastian; Bzdok, Jessica; Tesorero, Rafael; Holtkamp, Ute; Burggraf, Siegfried; Schuhmann, Elfriede; Hörster, Friederike; Hoffmann, Georg F.; Janzen, Nils; Okun, Jürgen G.; Becker, Marc; et al. (Klinische Pädiatrie, 2023)
Background: Sickle cell disease (SCD) is a group of hemoglobinopathies with a common point mutation causing the production of sickle cell hemoglobin (HbS). In high-throughput newborn screening (NBS) for SCD, a two-step procedure is suitable, in which qPCR first pre-selects relevant samples that are differentiated by a second method. Methods: Three NBS centers using qPCR-based primary screening for SCD performed a laboratory comparison. Methods using tandem MS or HPLC were used for differentiation. Results: In a benchmarking test, 450 dried blood samples were analyzed. Samples containing HbS were detected as reliably by qPCR as by methods established for hemoglobinopathy testing. In a two-step screening approach, the 2nd-tier-analyses have to distinguish the carrier status from pathological variants. In nine months of regular screening, a total of 353,219 samples were analyzed using two-stage NBS procedures. The 1st-tier screening by qPCR reduced the number of samples for subsequent differentiation by >99.5%. Cases with carrier status or other variants were identified as inconspicuous while 78 cases with SCD were revealed. The derived incidence of 1:4,773, is in good agreement with previously published incidences. Conclusion: In high-throughput NBS for SCD, qPCR is suitable to focus 2nd-tier analyses on samples containing HbS, while being unaffected by factors such as prematurity or transfusions. The substantial reduction of samples numbers positively impacts resource conservation, sustainability, and cost-effectiveness. No false negative cases came to attention.